Change in depressive symptom scores to assess the risk of new-onset dual sensory impairment in middle-aged and older adults: a nationwide cohort study - Jiang Wang; Jiang Wang; Lanzhi Duan; Lanzhi Duan; Rui Zeng; Fayi Xie; Zhigang Wu; Zhigang Wu; Yanhong Luo; Yanhong Luo; Xiaoming Zhang; Wei Li; et al. (Frontiers in Public Health)
BackgroundEvidence of the association between change in depressive symptom scores and new-onset dual sensory impairment (DSI) remain underexplored. We aimed to investigate the relationship between depressive symptom scores and the risk of new-onset DSI in middle-aged and older adults.MethodsThe study included 3,237 participants. The Center for Epidemiologic Studies Depression Scale (CES-D-10) was used to assess depression symptoms. CES-D-10 scores were classified according to the K-means cluster analysis. Subsequently, the logistic regression analysis was used to determine the association between the change in CES-D-10 scores and DSI. Additionally, restricted cubic splines (RCS) were employed to examine whether there was a linear correlation between cumulative CES-D-10 scores and DSI. We also explored whether the association of CES-D-10 scores with DSI varies across different subgroups.ResultsOne thousand and sixty one out of 3,237 participants had a new-onset DSI during 3 years. Compared to class 1 with the best control of depressive state, the OR for class 2 with good control was 1.54 (95% CI, 1.28, 1.85), the OR for class 3 with moderate control was 1.59 (95% CI, 1.22, 2.07), the OR for class 4 with worse control was 1.62 (95% CI, 1.31, 2.02), and the OR for class 5 with consistently high levels was 1.86 (95% CI, 1.34, 2.57).ConclusionsIndividuals exhibiting suboptimal management of depressive symptoms were more susceptible to developing new-onset DSI, underscoring the need for early depression screening and assessment in the preventative strategies for new-onset DSI.